Transcriptomic Data Of Mature Oil Palm Basal Trunk Tissue Infected With Ganoderma Boninense - Nur Qistina Othman; Suhaila Sulaiman; Yang Ping Lee; Joon Sheong Tan (Elsevier, 2024)
Data in Brief Volume 25, August 2019, 104288